Determine Effectiveness of cotton Seed Cleaning and Sorting Machines: Menentukan Efektivitas Mesin Pembersih dan Sortasi Benih Kapas - Sardorbek Sandjarovich Isroilov (Academia Open, 2022)
This scientific article presents a comprehensive exploration of seed cleaning techniques, emphasizing the incorporation of aerodynamic sorting and multi-factional sorting as means to achieve optimal seed purity and prevent seed damage while enhancing fiber yield for textile industry applications. The study outlines the goals, methods, results, and implications of scientific research conducted to improve seed cleaning technology. By employing advanced cleaning methods, complete elimination of impurities from ginnated seeds is made possible, thereby ensuring a productive and high-quality seed yield suitable for spinning in the textile industry. The findings and recommendations of this research offer valuable insights for global scientists and industry professionals seeking to enhance seed cleaning processes, maximize productivity, and meet the demands of the textile industry. Highlights: Improved Seed Quality: Incorporating aerodynamic sorting and multi-factional sorting techniques enhances seed cleaning, resulting in impurity-free seeds suitable for high-quality fiber production in the textile industry. Preventing Seed Damage: Advanced seed cleaning technology minimizes the risk of seed damage during the cleaning process, ensuring optimal seed integrity and viability for improved germination and yield. Increased Fiber Productivity: Efficient seed cleaning methods increase fiber yield, providing a sustainable source of high-quality fibers for the textile industry, thereby meeting the growing demand for textile materials. Keywords: seed cleaning, aerodynamic sorting, multi-factional sorting, impurity-free seeds, fiber yield.